2018
DOI: 10.3390/ijerph15102165
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Access to Rehabilitation for People with Disabilities in Low- and Middle-Income Countries

Abstract: Rehabilitation seeks to optimize functioning of people with impairments and includes a range of specific health services—diagnosis, treatment, surgery, assistive devices, and therapy. Evidence on access to rehabilitation services for people with disabilities in low- and middle-income countries (LMICs) is limited. A systematic review was conducted to examine this in depth. In February 2017, six databases were searched for studies measuring access to rehabilitation among people with disabilities in LMICs. Eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
157
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(181 citation statements)
references
References 78 publications
6
157
0
18
Order By: Relevance
“…We tested for two hierarchical levels of statistical significance: 99 and 95%, respectively. On Age-standardized YLD Rates, which adjusted YLDs for population size and ageing, Table 2 shows that only high-income and lower middle-income countries had a significant change since 1990, but while the latter had a linear growth ( LMICs remain quite limited [7,19,26,83,84]. The WHO estimates that skilled rehabilitation professionals for many LMICs are currently about one-tenth of those required [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested for two hierarchical levels of statistical significance: 99 and 95%, respectively. On Age-standardized YLD Rates, which adjusted YLDs for population size and ageing, Table 2 shows that only high-income and lower middle-income countries had a significant change since 1990, but while the latter had a linear growth ( LMICs remain quite limited [7,19,26,83,84]. The WHO estimates that skilled rehabilitation professionals for many LMICs are currently about one-tenth of those required [7].…”
Section: Discussionmentioning
confidence: 99%
“…The WHO estimates that skilled rehabilitation professionals for many LMICs are currently about one-tenth of those required [7]. Hence, many argue it is urgent to take action to supply LMICs with increased resources, [24,26,[83][84][85][86][87] and especially so given the higher nominal increases of physical rehabilitation needs.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the current level of access to hearing specific services is inadequate in LMICs [19,20]. A recent systematic review of access to rehabilitation for people with disabilities found that coverage of assistive devices for people with hearing loss was unacceptably low across LMICs where data existed, ranging from 0 to 24% at the population-level [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 15% of the global population-1 billion people-are living with a disability, with the majority residing in low and middle-income countries [1]. As a group, people with disabilities face an increased risk of poverty and social exclusion, due to barriers to participating in paid work and education, negative attitudes towards disability, inaccessible environments and information, extra disability-related costs (e.g., assistive devices, personal assistance), and lack of affordable, quality disability-related services and support [1][2][3][4]. The United Nations Convention on the Rights of People with Disabilities (UNCRPD), which has been ratified by 177 countries, codifies the rights of people with disabilities to full inclusion on an equal basis as others [5,6].…”
Section: Introductionmentioning
confidence: 99%